Stochastic Dilated Residual Ghost Model for Breast Cancer Detection. - Kashyap, Ramgopal (Journal of Digital Imaging, 2023)
One of the most contentious issues in modern medicine is how to effectively standardise breast cancer screening. Deep learning models are already saving lives in the medical field due to their capacity to distinguish between benign and malignant tumours. Histopathology imaging poses difficulties due to the possibility of large colour variations caused by the staining technique and the biopsy material used to make the image; this problem leads to inaccurate breast cancer diagnoses. Our primary focus in this assessment is on the four main research concerns listed in the following: Overfitting and colour divergence must be rectified before moving on to other aspects of breast cancer categorisation. To overcome this issue, strain normalisation is utilised, and adding extra components is used to cope with overfitting; both techniques yielded positive results. The multiscale stochastic and dilation unit was then created to extract and enhance fine-grained characteristics such as edges, contours, and colour accuracy. To achieve this, the image is scaled to various different levels. The last challenge is to overcome the stochastic dilated residual ghost model's unreliability when used to recognise very tiny objects. The stochastic pooling block in this model makes effective use of downsampling to simplify the process without compromising the capacity to retrieve deep information. This upgrade was done as part of a bigger endeavour to eliminate unneeded or redundant components. In this case, we use convolution and identity mapping to create and maintain accurate mappings of the object's inherent characteristics. Upsampling is frequently used in conjunction with stochastic pooling to reduce feature dimensionality. The results of the experiments show that the suggested method is better than some of the current methods, with a network performance measurement area under the curve of 96.15 and percentages of 98.50 and 97.36.